Harmonious Environmental Passion Mediating Green HRM, Self-Efficacy, and Values - Evi silvana muchsinati; Tiffanny Tiffanny; Ratih Anggraini; Yuddy Giovanna (Jurnal Manajemen, 2026)
The service sector, especially hospitality, faces sustainability challenges from regulations and consumer demands. GHRM is a key strategy to promote green behavior and sustainable performance. This study examines Harmonious Environmental Passion (HEP) as a mediator between GHRM and Green Self-Efficacy (GSE), with Green Values (GV) as a moderator. A quantitative survey of 280 employees from four and five-star hotels in Batam was analyzed using PLS-SEM via Smart PLS 4, including validity, reliability, path coefficients, and indirect effects tests. Results show GHRM significantly affects GSE and HEP. HEP mediates the GHRM-GSE relationship, and GV strengthens it. The study highlights the emotional role of HEP in GHRM effectiveness in hospitality.